It is recreational but profitability also matters: A cost-effective economic approach to marine recreational fishing in Spain - GORDOA, ANA (Mediterranean Marine Science, 2023)
This study analyses the costs of marine recreational activity in Spain for the main fishing modalities and provides a cost-effective economic indicator (CEI) for each of them. The activity costs of 4,999 fishers were collected through an online survey, along with other fishing information. The published results of this survey, catch rates and catch composition, have been used in this study. Daily expenses per fisher were estimated by dividing reported annual expenses by annual fishing days. The CEI was estimated as the ratio of the market value of one kilo of recreational catch to the cost of catching it. The CEI showed differences between modalities in all regions, but of varying magnitudes. It is concluded that the CEI could diagnose the risk level of evolving from recreational towards subsistence fishing. The higher the CEI, the more compensatory the activity and the greater the possibility of moving away from a purely recreational activity in adverse economic conditions.